Molecular Features and Expression Patterns of Vitellogenin Receptor in Calliptamus italicus (Orthoptera: Acrididae). Issue 6 (8th December 2019) - Xiang, Min; Sang, Di; Dong, Bin; Hu, Hongxia; Ji, Rong; Wang, Han
Abstract: Vitellogenin receptor (VgR) mediates the intake of vitellin via oocytes, thus exerting an important role in vitellogenesis. In this study, reverse transcription-polymerase chain reaction (RT-PCR) and rapid-amplification of cDNA ends techniques were adopted to clone the CiVgR gene, namely the VgR gene of Calliptamus italicus, i.e., Orthopteran. The full length of CiVgR was 5, 589 bp, and the open reading frame was estimated to be 5, 265 bp, which encoded 1, 754 amino acids (aa). Sequence alignment analysis showed that CiVgR belonged to the superfamily of low-density lipoprotein receptor genes, which contained several conserved domains, including ligand-binding domains, epidermal growth factor precursor homology domains, transmembrane domains, and cytoplasmic domains. However, no O-linked sugar domain was identified. Phylogenetic analysis showed that CiVgR had the closest genetic relationship to Blattarias. RT-PCR showed that CiVgR was only specifically expressed in the ovarian tissue of females. quantitative real time polymerase chain reaction showed that the transcription of CiVgR already appeared in the fourth-instar nymph of C. italicus, which gradually increased after adult emergence, peaked at the previtellogenesis stage, and then started to decrease. The expression pattern of CiVgR was closely associated with vitellogenesis. The findings of this study further our understanding of the molecular mechanisms involved in the reproduction of C. italicus, and provide new ideas to control this insect.